Effects of choice architecture and the anchoring-and-adjustment heuristic on pro-social and pro-environmental e-commerce consumer behaviour - Lee, Shannen Si En (Nanyang Technological University, 2023)
Consumers are encouraged to do their part in protecting the environment by consuming sustainably and purchasing products that have a lower environmental impact. However, challenges such as a lack of information on eco-friendly products, time constraints, and pre-existing brand preferences, could hinder consumers from selecting eco-friendly choices. Previous studies have shown that the way information is presented can affect consumers’ decision-making processes, and thereby, promote pro-social and pro-environmental purchasing behaviour. Our research applies heuristics in the context of encouraging eco-friendly online shopping. The objective of this study was to explore whether nudges, particularly in the form of eco-labels and social comparison nudges, could help people choose the more sustainable product, despite having other products anchored as the default option. An online experiment (n = 262) was conducted to investigate the effects of anchoring, which causes biases in decision making; and nudging, to encourage pro-environmental purchasing decisions on e-commerce behaviour. Results showed that there were significant main and interaction effects of both anchoring and nudging, reaffirming the use of nudges to encourage pro-environmental behaviour in e-commerce. The paper discussed further usage of nudges and anchors, as well as implications on user experience design in the e-commerce industry.